2001
DOI: 10.1097/00006534-200111000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Postauricular Fascial Flap as an Adjunct to Mustardé and Furnas Type Otoplasty

Abstract: Anterior riberation methods of otoplasty have been criticized because of the risk of anterior hematoma that can cause anterior skin necrosis, scarring, and even cartilage destruction caused by infection. As a result, cartilage-sparing otoplasty such as the Mustardé and Furnas types has been increasingly popular. However, postauricular suture extrusion may result, and recurrence rates of up to 25 percent have been recorded. In this study, cartilage-sparing otoplasty is refined by the addition of a postauricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 11 publications
1
40
1
1
Order By: Relevance
“…3e6 Instead, cartilage-sparing techniques using Mustardé and Furnas type sutures have been shown to yield significantly more favourable outcomes. 9 This is in keeping with the experience from our unit. We have previously published our results 3,4 comparing outcomes from different otoplasty techniques, and shown that posterior suturing with posterior fascial otoplasty, as described by Horlock, Misra and Gault in 2001, are consistently superior to anterior scoring or posterior suturing alone, both in terms of reduced complication and clinical recurrence rates and improved patient and parent satisfaction.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…3e6 Instead, cartilage-sparing techniques using Mustardé and Furnas type sutures have been shown to yield significantly more favourable outcomes. 9 This is in keeping with the experience from our unit. We have previously published our results 3,4 comparing outcomes from different otoplasty techniques, and shown that posterior suturing with posterior fascial otoplasty, as described by Horlock, Misra and Gault in 2001, are consistently superior to anterior scoring or posterior suturing alone, both in terms of reduced complication and clinical recurrence rates and improved patient and parent satisfaction.…”
Section: Discussionsupporting
confidence: 79%
“…Skin excision during otoplasty was advocated by Horlock in his original 2001 paper 9 and dates back to the publications by Mustardé and Furnas in 1978. 7,8 Though it was never specifically explained, it is reasonable to assume that the rationale behind skin excision is (1) to address any relative skin redundancy resulting from setting back the ear and (2) to reduce the chances of recurrence of the ear prominence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-auricular proximal-based fascial flap, illustrated by Horlock et al (24), combined with posterior suturing has been demonstrated to be the method with the lowest recurrence and least complication rates by Schaverien et al (25). In a follow-up period of 3.9 years (range: 1.5-7.8), the clinical recurrence rate was 4.5%.…”
Section: Discussionmentioning
confidence: 99%